A high thermal shock MgO-Al-C skateboard brick and its preparation method

By adding light zirconia particles to the MgO-Al-C skateboard, and utilizing its microporous structure and phase change toughening effect, the problems of thermal expansion and insufficient bonding strength of magnesia particles are solved, and the thermal shock resistance of the skateboard is significantly improved. and high temperature strength, extending service life.

CN114932213BInactive Publication Date: 2025-01-21HENAN UNIVERSITY OF TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210714837.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-23
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The thermal expansion coefficient of magnesium sand particles in MgO-Al-C skateboards is large, which affects thermal shock resistance, and the bonding strength between the particles and the matrix is ​​weak, affecting the high temperature strength and resulting in a reduced service life.

Method used

MgO-Al-C skateboard tiles containing light zirconia particles are used. By adding 1 to 8% light zirconia particles to the raw materials, its microporous structure and phase change toughening effect are used to absorb the thermal expansion and improvement of magnesia. The degree of bonding of materials.

Benefits of technology

Significantly improves the thermal shock resistance and high-temperature strength of the skateboard, reduces the frequency of cracks, peeling and linting at high temperatures, and extends the service life of the skateboard.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a high thermal shock MgO-Al-C skateboard brick and a preparation method thereof. In terms of weight percentage, the raw material composition is: 55-65% magnesia particles, 20-35% magnesia fine powder, 5-10% metal aluminum, 1-8% light zirconia particles, 1-3% carbon-containing raw materials, 0.5-5% additives, and 3-5% binders. Each component is weighed by weight, and after mixing, molding, baking, or continuing to be treated at medium temperature in a weak reducing atmosphere or nitrogen atmosphere, it is put into storage after being hooped, glued to a steel shell, ground, coated, finished, and accepted. The high thermal shock MgO-Al-C skateboard brick produced by the present invention is added with light zirconia particles with micropores and compressibility, which absorbs the thermal expansion of magnesia, relieves the thermal stress of the material, and improves the thermal shock resistance. At high temperature, the zirconia particles and periclase are solid-dissolved, which promotes the combination of materials, increases the high temperature strength, reduces the degree of cracking, peeling, and roughening during use, and improves the service life of the MgO-Al-C skateboard.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a slide brick for steelmaking continuous casting, in particular to a MgO-Al-C slide brick containing light zirconium oxide particles and a preparation method thereof, belonging to the field of production of slide bricks for steelmaking. Background Art

[0002] Slide plates are used in steelmaking and continuous casting to regulate and control the flow of molten steel, or in the slag blocking and steel tapping system of the converter to improve the slag blocking effect. With the development of special steel, calcium treatment of molten steel has become inevitable. Traditional aluminum-zirconium-carbon slide plates have serious melting losses when pouring calcium-treated steel, and zirconium slide plates are expensive. Magnesium slide plates have good corrosion resistance to calcium-treated steel and are low in cost. Therefore, high-temperature fired magnesia, magnesium spinel, and unfired MgO-MA-C and MgO-Al-C slide plates have been developed one after another. Although the MgO-Al-C slide plate has achieved relatively good results, it still has problems such as poor thermal shock resistance and low high-temperature strength. Due to the large thermal expansion coefficient of periclase (13.5×10 -6 ℃ -1 ), resulting in poor thermal shock resistance, and problems such as cracks, peeling, and roughening are prone to occur during steel casting, affecting the service life. Therefore, in order to improve the thermal shock resistance of MgO-Al-C slide plates, the thermal expansion of magnesia particles must be absorbed. There are two main measures to improve the thermal shock resistance of materials: one is to inhibit the generation of cracks; the other is to prevent crack propagation. At high temperatures, when zirconia undergoes a martensitic phase transformation from monoclinic ZrO2 to tetragonal ZrO2, there is a volume shrinkage of about 5%, which can relieve thermal stress and inhibit crack generation; on the contrary, when it transforms from tetragonal ZrO2 to monoclinic ZrO2, there is a volume expansion of about 8%, which can absorb the diffusion energy at the crack tip, prevent crack propagation, and play a toughening role. Since magnesium oxide is a stabilizer for zirconium oxide, if zirconium oxide fine powder is added to magnesium materials, zirconium oxide is transformed into stable cubic zirconium oxide at high temperatures, and its phase transformation toughening effect cannot be exerted, and the effect on improving the thermal shock resistance of magnesium materials is not obvious. Therefore, it is necessary to introduce zirconium oxide raw materials with special structure to absorb the thermal expansion of magnesia particles, dissipate thermal stress, and improve the thermal shock resistance of MgO-Al-C slide plates. Summary of the invention

[0003] The technical problem to be solved by the present invention is: in view of the technical problems that the thermal expansion coefficient of magnesia sand particles in the MgO-Al-C skateboard is large, which affects the thermal shock resistance, and the bonding strength between the particles and the matrix is ​​weak, which affects the high-temperature strength and reduces the service life, a high thermal shock MgO-Al-C skateboard brick and a preparation method thereof are provided.

[0004] The technical solution adopted by the present invention to solve the technical problem is:

[0005] A high thermal shock MgO-Al-C skateboard brick. The raw material composition of the skateboard brick is as follows: 55-65% of magnesia particles, 20-35% of magnesia fine powder, 5-10% of metal aluminum, 1-8% of light zirconium oxide particles, 1-3% of carbon-containing raw materials, 0.5-5% of additives, and 3-5% of binders, calculated by weight percentage.

[0006] Preferably, the magnesia particles and magnesia fine powder are one of fused magnesia and sintered magnesia, or a combination of the two.

[0007] Preferably, the composition of the magnesia particles is as follows: magnesia particles with a particle size of 1 to 3 mm account for 40 to 55%, and magnesia particles with a particle size less than 1 mm account for 10 to 20%; the particle size of the magnesia fine powder is less than 0.088 mm.

[0008] Preferably, the metal aluminum is one or a combination of aluminum powder and aluminum fiber.

[0009] Preferably, the light zirconia particles are a combination of one or more of granulated zirconia micropowder, zirconia hollow microbeads and porous structure light raw materials; the particle size of the light zirconia particles is 0.1-0.5 mm.

[0010] Preferably, the carbon-containing raw material is a combination of one or more of carbon black, graphite, expanded graphite, asphalt powder and resin powder.

[0011] Preferably, the additive is a combination of one or more of elemental silicon, silicon carbide, boron carbide, silicon-aluminum alloy, magnesium-aluminum alloy, and boron-magnesium alloy.

[0012] Preferably, the binder is one of phenolic resin, modified phenolic resin and silicone resin, or a combination of the two.

[0013] A method for preparing a high thermal shock MgO-Al-C skateboard brick, the specific steps of which are as follows:

[0014] A. Weigh the following raw materials by weight percentage: 55-65% magnesia particles, 20-35% magnesia fine powder, 5-10% metallic aluminum, 1-8% light zirconium oxide particles, 1-3% carbon-containing raw materials, 0.5-5% additives, and 3-5% binder.

[0015] B. Evenly mix the metallic aluminum, magnesia powder, carbon-containing raw materials and additives to make mixed powder in a double cone mixer.

[0016] C. Add magnesia particles and light zirconium oxide particles into a mixer and mix them evenly. Take a binder and add 2 / 3 of the amount first to mix it with the particles and fully coat the particles. Then add the mixed powder prepared in step B and the remaining 1 / 3 of the binder and mix them further.

[0017] D. The mixed material in step C is trapped for 12 to 24 hours, pressed into shape, and the formed body is baked at 180°C to 220°C for 48 hours, or placed in a furnace after baking, and subjected to medium temperature treatment at 550°C to 800°C for 12 hours in a weak reducing atmosphere or nitrogen atmosphere, and then put into storage after hooping, steel shell bonding, grinding, coating, finishing, acceptance, and inspection.

[0018] The positive beneficial effects of the present invention are as follows:

[0019] 1. Lightweight zirconium oxide particles are added to the high thermal shock MgO-Al-C skateboard bricks prepared by this patent. Since the particles have a microporous structure and are compressible, they can absorb the thermal expansion of magnesia, relieve the thermal stress of the material, and improve its thermal shock resistance. The zirconium oxide on the surface of the particles is stabilized by magnesium oxide, but the interior is still a monoclinic phase, which plays a phase change toughening role and increases thermal shock stability.

[0020] 2. The high thermal shock MgO-Al-C skateboard bricks prepared in this experiment, the light zirconium oxide particles and the surrounding magnesia sand form a MgO-ZrO2 solid solution at high temperature, which increases the bonding degree of the material and improves the high temperature strength.

[0021] 3. The MgO-Al-C slide produced by this patent has good thermal shock resistance and high high temperature strength, which reduces the degree of cracking, peeling and roughening during use and increases the service life of the slide. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with embodiments:

[0023] Example 1

[0024] The weight ratio of each raw material is: sintered magnesia particles with a particle size of 1 to 3 mm ( w (MgO) ≥ 97.70%) accounted for 52%, and the particle size was less than 1 mm fused magnesia particles ( w (MgO) ≥ 98.00%) accounts for 10%, and the particle size is less than 0.088 mm fused magnesia fine powder ( w (MgO) ≥ 98.00%) accounts for 25%, and the aluminum powder with a particle size less than 0.088 mm ( w (Al) ≥ 98.50%) accounts for 8%, carbon black with a particle size of 25-20 nm ( w (C) ≥ 99.50%) 0.5%, graphite with a particle size of less than 0.045 mm ( w (C) ≥ 97.00%) accounts for 1.5%, and the particle size is less than 0.2 mm granulated zirconium oxide powder ( w (ZrO2) ≥ 98.70%) accounts for 2%, and the particle size of boron carbide is less than 0.045mm (w (B4C)≥95.00%) accounts for 1%, and 3% of the binder is a mixed solution of 1.5% phenolic resin and 1.5% silicone resin.

[0025] The specific preparation method of the high thermal shock MgO-Al-C skateboard brick is as follows:

[0026] 1) Aluminum powder, fused magnesia powder, carbon black, graphite and boron carbide are uniformly mixed to make mixed powder in a double cone mixer.

[0027] 2) adding magnesia particles and granulated zirconium oxide powder into a mixer and mixing them evenly, taking a binder, first adding 2 / 3 of the amount thereof, mixing it with the particles thoroughly, and then adding the mixed powder prepared in the above step 1) and the remaining 1 / 3 of the binder, and further mixing them thoroughly;

[0028] 3) The mixed material in step 2) is trapped for 16 hours, pressed into shape, and the formed body is baked at 200℃ for 48 hours, then placed in a furnace and subjected to medium temperature treatment at 750℃×12 hours in a weak reducing atmosphere, and then put into storage after hooping, steel shell bonding, grinding, coating, finishing, acceptance, etc. The performance indicators of the prepared high thermal shock MgO-Al-C skateboard brick are: apparent porosity 12.1%, volume density 2.95 g·cm -3 The high temperature flexural strength of the carbon buried at 1400℃ for 0.5 h is 29.6MPa, and the residual strength retention rate is 60% after air cooling at 1100℃ for 3 times.

[0029] Example 2

[0030] The weight ratio of each raw material is: fused magnesia particles with a particle size of 1 to 3 mm ( w (MgO) ≥ 98.00%) accounted for 48%, and the sintered magnesia particles with a particle size of less than 1 mm ( w (MgO) ≥ 97.70%) accounts for 15%, and the sintered magnesia fine powder with a particle size of less than 0.088 mm ( w (MgO) ≥ 97.70%) accounts for 20%, and the aluminum powder with a particle size less than 0.088 mm ( w (Al) ≥ 98.80%) accounts for 10%, and the particle size of carbon black is 25-20 nm ( w (C) ≥ 99.50%) 1%, graphite with a particle size of less than 0.045 mm ( w (C)≥97.00%) accounts for 1%, and the particle size is less than 0.5 mm zirconia hollow microspheres ( w (ZrO2) ≥ 98.50%) accounts for 4%, and the particle size of boron carbide is less than 0.045mm ( w(B4C)≥95.00%) accounts for 1%, and 3% of the binder is: a mixed solution of 1.5% modified phenolic resin and 1.5% silicone resin.

[0031] The specific preparation method of the high thermal shock MgO-Al-C skateboard brick is as follows:

[0032] 1) Magnesia fine powder, aluminum powder, carbon black, graphite and boron carbide are mixed evenly and blended into mixed powder in a double cone mixer.

[0033] 2) Add magnesia particles and zirconia hollow microspheres into a mixer and mix them evenly. Take a binder and add 2 / 3 of it first, mix it with the particles thoroughly, and fully coat the particles. Then add the mixed powder prepared in the above step 1) and the remaining 1 / 3 of the binder, and further mix them thoroughly.

[0034] 3) The mixed material in step 2) is trapped for 24 hours, pressed into shape, and the formed green body is baked at 220°C for 48 hours, then put into storage after hooping, steel shell bonding, grinding, coating, finishing, acceptance, etc. The performance indicators of the prepared high thermal shock MgO-Al-C skateboard brick are: apparent porosity 11.6%, volume density 2.97 g·cm -3 The high temperature flexural strength of the carbon buried at 1400 ℃ and kept at this temperature for 0.5 h is 32.3MPa, and the residual strength retention rate is 65% after air cooling at 1100 ℃ for 3 times.

[0035] Example 3

[0036] The weight ratio of each raw material is: sintered magnesia particles with a particle size of 1 to 3 mm ( w (MgO) ≥ 97.70%) accounted for 48%, and the sintered magnesia particles with a particle size of less than 1 mm ( w (MgO) ≥ 97.70%) accounts for 17%, and the fused magnesia fine powder with a particle size of less than 0.088 mm ( w (MgO) ≥ 98.00%) accounted for 21%, and the aluminum powder with a particle size less than 0.088 mm ( w (Al) ≥ 98.50%), 6%, aluminum fiber with a diameter of 60 μm and a length of 3 mm ( w (Al) ≥ 99.00%) accounts for 1%, and the graphite with a particle size less than 0.045 mm ( w (C) ≥ 97.00%) accounted for 2%, and the zirconia hollow microspheres with a particle size of less than 0.5 mm ( w (ZrO2)≥98.60%) accounts for 2%, and the particle size is less than 0.2 mm granulated zirconium oxide powder ( w (ZrO2)≥98.50%) accounts for 1%, and the particle size is less than 0.045 mm. w(Si) ≥ 98.00%) accounts for 2%, and 3% binder is added: a mixed solution of 2% phenolic resin and 1% silicone resin.

[0037] The specific preparation method of the high thermal shock MgO-Al-C skateboard brick is as follows:

[0038] 1) Magnesia fine powder, aluminum powder, graphite and elemental silicon are mixed evenly and blended into mixed powder in a double cone mixer.

[0039] 2) Add magnesia particles, hollow zirconium oxide microspheres, and granulated zirconium oxide powder into a mixer and mix them evenly. Take a binder and add 2 / 3 of it first, mix it with the particles thoroughly, and fully coat the particles. Then add the mixed powder prepared in step 1) and the remaining 1 / 3 of the binder and mix them thoroughly. Add aluminum fiber and mix evenly.

[0040] 3) The mixed material in step 2) is trapped for 16 hours, pressed into shape, and the formed body is baked at 200°C for 48 hours, or placed in a furnace after baking, and subjected to medium temperature treatment at 650°C × 12 hours in a nitrogen atmosphere, and then put into storage after hooping, steel shell bonding, grinding, coating, finishing, acceptance, and acceptance. The performance indicators of the prepared high thermal shock MgO-Al-C skateboard brick are: apparent porosity 12.0%, volume density 2.96 g·cm -3 The high temperature flexural strength of the carbon buried at 1400 ℃ and kept at this temperature for 0.5 h is 35.2MPa, and the residual strength retention rate is 62% after air cooling at 1100 ℃ for 3 times.

Claims

1. A high thermal shock MgO-Al-C skateboard brick, characterized in that: The raw material composition of the skateboard brick is as follows: 55-65% magnesia particles, 20-35% magnesia fine powder, 5-10% metal aluminum, 1-8% light zirconium oxide particles, 1-3% carbon-containing raw materials, 0.5-5% additives, and 3-5% binders by weight percentage; The composition of the magnesia particles is as follows: magnesia particles with a particle size of 1 to 3 mm account for 40 to 55%, and magnesia particles with a particle size less than 1 mm account for 10 to 20%; the particle size of the magnesia fine powder is less than 0.088 mm; The metal aluminum is one of aluminum powder and aluminum fiber or a combination of the two; The light zirconium oxide particles are a combination of one or more of granulated zirconium oxide powder, hollow zirconium oxide microbeads and / or porous zirconium oxide raw materials; The particle size of the light zirconium oxide particles is 0.1-0.5 mm; The carbon-containing raw material is a combination of one or more of carbon black, graphite, expanded graphite, asphalt powder, and resin powder; The additive is a combination of one or more of elemental silicon, silicon carbide, boron carbide, silicon-aluminum alloy, magnesium-aluminum alloy, and boron-magnesium alloy; The binder is one of phenolic resin, modified phenolic resin and silicone resin or a combination of the two; The magnesia particles and magnesia fine powder are a combination of fused magnesia and sintered magnesia; The specific steps of the preparation method of the high thermal shock MgO-Al-C skateboard brick are as follows: A. Weigh the following raw materials by weight percentage: 55-65% magnesia particles, 20-35% magnesia fine powder, 5-10% metallic aluminum, 1-8% light zirconium oxide particles, 1-3% carbon-containing raw materials, 0.5-5% additives, and 3-5% binder; B. Evenly mix the metal aluminum, magnesia powder, carbon-containing raw materials and additives to make mixed powder in a double cone mixer; C. Add magnesia particles and light zirconium oxide particles into a mixer and mix them evenly. Take a binder and add 2 / 3 of the amount first to mix it with the particles and fully coat the particles. Then add the mixed powder prepared in step B and the remaining 1 / 3 of the binder and mix them further. D. The mixed material in step C is trapped for 12 to 24 hours, pressed into shape, and the formed body is baked at 180°C to 220°C for 48 hours, or placed in a furnace after baking, and subjected to medium temperature treatment at 550°C to 800°C for 12 hours in a weak reducing atmosphere or nitrogen atmosphere, and then put into storage after hooping, steel shell bonding, grinding, coating, finishing, acceptance, and inspection.

2. A method for preparing a high thermal shock MgO-Al-C skateboard brick, the specific steps of which are as follows: A. Weigh the following raw materials by weight percentage: 55-65% magnesia particles, 20-35% magnesia fine powder, 5-10% metallic aluminum, 1-8% light zirconium oxide particles, 1-3% carbon-containing raw materials, 0.5-5% additives, and 3-5% binder; B. Evenly mix the metal aluminum, magnesia powder, carbon-containing raw materials and additives to make mixed powder in a double cone mixer; C. Add magnesia particles and light zirconium oxide particles into a mixer and mix them evenly. Take a binder and add 2 / 3 of the amount first to mix it with the particles and fully coat the particles. Then add the mixed powder prepared in step B and the remaining 1 / 3 of the binder and mix them further. D. The mixed material in step C is trapped for 12 to 24 hours, pressed into shape, and the formed body is baked at 180°C to 220°C for 48 hours, or placed in a furnace after baking, and subjected to medium temperature treatment at 550°C to 800°C for 12 hours in a weak reducing atmosphere or nitrogen atmosphere, and then put into storage after hooping, steel shell bonding, grinding, coating, finishing, acceptance, and inspection.

Citation Information

Patent Citations

  • Slide gate brick and preparation method thereof

    CN105967702A

  • Magnesia carbon brick with high thermal shock resistance

    CN112759369A

  • Low-thermal-conductivity spinel refractory homogeneous brick as well as preparation method and application thereof

    CN113443898A